Privacy concerns and protection motivation theory in the context of mobile banking - Terlizzi, Marco Alexandre (2019)
Nearly 100% of Americans aged 18 to 29 own a cell phone of some kind, and there has been a move toward using mobile devices for financial services; however, such a move also implies increased opportunities for fraud. Although technology has traditionally been blamed for showing some vulnerabilities, the literature recognizes that human behavior is still the most vulnerable link in an information security system, as it facilitates the discovery of personal identity, account numbers, and passwords, thus often leading to successful financial scams. Protection motivation theory (PMT) is naturally suited to information security contexts in which fear motivates users to protect their information assets; thus, we propose that it can also be meaningfully applied to a privacy context. We addressed four literature gaps: the lack of real-time technology for measuring fear; the omission of a full nomology of PMT as an antecedent of privacy concerns (PC); the omission of fear appeal manipulations in PC; and no reuse of the most up-to-date PC scale. The purpose of this thesis is to examine how PMT can be used in combination with PC in the context of mobile banking (m-banking) and its consequences for risk, trust, and intention to use. We tested our model in four different studies (grouped in three papers): two online surveys, one online experiment, and one lab experiment using emotion detection technology. We found that when an m-banking user is stimulated by a fear appeal message, the fear of losing information increases, consequently activating PC and inducing the user to use the platform more securely. We also contribute to the privacy literature by motivating and studying the relationship between fear and PC.